Pengaruh Motivasi & Imbalan Kerja Terhadap Kinerja Karyawan CV. Kemenangan Jaya - Widiawati Widiawati; Etika Sabariah (STIKes Ibnu Sina Ajibarang, 2023)
The background in this study is how important a leader is in applying motivation and work rewards to the company to improve the performance of his employees, because with motivation and work discipline, employees will feel responsible for all their duties. This study aims to determine the effect of work motivation and work rewards on employee performance partially, and to determine the effect of work motivation and work discipline on employee performance simultaneously. The conclusion from the results of this study is that increasing employee performance is inseparable from Work Motivation (needs, attitudes, abilities, payment or salary, job security, relationships with fellow workers), work rewards (providing overtime or wages given to employees) and employee performance (always arriving on time, always prioritizing attendance percentage, always obeying the provisions of working hours, always using working hours effectively and efficiently).